CURRENT SITUATION OF THE INTEGRATION OF ENGLISH FOR SPECIFIC PURPOSE IN ENGLISH SUBJECT MATERIALS FOR TOURISM DEPARTMENT - Dahlia Husain; Moon Hidayati Otoluwa; Bahar Bahar (British (Jurnal Bahasa dan Sastra Inggris), 2023)
This research aims to discover how English for Specific Purposes served the English subject materials at the Tourism department in tertiary education. A needs analysis is carried out to gain information about the student’s perception of English teaching and learning status in the Tourism department. The study's design is descriptive quantitative with a perceptional questionnaire as the primary research data collection instrument. The research participants were the students of the Tourism Department at the Muhammadiyah University of Gorontalo. The results showed that Tourism department students at the Muhammadiyah University of Gorontalo used textbooks that were still oriented towards general English, were not made for their specific department, and were not suited to their level of English mastery. Besides the motivation of students to learn English, the correlation of the English they learn with the needs of English for future work and institutional support also deserves attention. Therefore, developing ESP-based English teaching materials for Tourism students in tertiary institutions becomes a priority.